Instructional Materials and Their Influences on Students’ Academic Performance: A Case of Post-Basic School English Curriculum in Burundi - Alfred Irambona; John K. Chang’ach (Journal of English Language Teaching and Linguistics, 2023)
This study investigates how instructional materials affect students' academic achievement in Burundi post-basic English curriculum. This paper is a report of part of research conducted in 2023 to evaluate the instructional influences of the post-basic school English curriculum on learners’ achievement in Burundi. This study utilized a convergent parallel research design and pragmatic paradigm, supported by Communicative Language Teaching for the 21st Century and the Social Learning Theory. To gather data from 16 English teachers and 330 language learners at the post-basic school level in the second and third years in the Bujumbura Municipality, a learners’ questionnaire, teachers’ interviews, and classroom observations were used. This study employed stratified and random sampling techniques to select respondents, and the data was analyzed descriptively and thematically. The study established that learners’ textbooks were level-appropriate, with 66.5% of the respondents understanding the content of the pupil’s textbook. The investigation also demonstrated the authenticity of the activities in the learners’ textbook since the developed themes were daily life-based issues. However, it was found that the learning activities were insufficient because some themes were not fully developed. The study further demonstrated that the majority of the sampled schools had an alarming scarcity of teaching materials including textbooks, and audio and audio-visual teaching aids. This research finally revealed that instructional materials had a moderate influence on students' academic achievement (overall mean = 3.257, SD =.6901). The government is advised to provide the missing teaching and materials to facilitate the smoother teaching and learning process and enhance students’ academic performance.